Memories and histories of Córdoba (Argentina): knowledge dialogue with older adults during pandemic (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This article seeks to recover the educational experience of a course for older adults carried out within the framework of a call for extension courses promoted by the Department of Philosophy and Humanities of Cordoba National University. The meetings were held online, taking the measures of shelter and caring that COVID-19 pandemic demanded. From a critic view position about extensionist practices, the text inquires about the bonds within older adults in extensionists contexts and the selection of contents based on the changes and possibilities offered by ICTs. The paper also recovers the decision-making process to structure the proposal and the challenges that arose during the different meetings. Continuous modifications were promoted to enable a place that guarantees the exchange and knowledge dialogue. We consider important to continue with this kind of initiatives that take consideration of older adults as active actors and bearers of acquaintance.
Keywords: Older Adults; knowledge dialogue; university extension work; Cordoba’s History; pandemic